Residential architectural development strategies in Kazakhstan - Uzakbayev, Turar; Kozhagulov, Tokkozha; Zhedelov, Kurmangazy; Sakenova, Saya; Amandykova, Dina (project baikal, 2026)
This article analyzes low-rise housing design solutions adapted to the conditions of foothill regions. The purpose of this study is to analyze the compliance of design solutions and completed residential projects with the new development regulations for the city of Almaty approved in 2025. The results demonstrate a transition to a human-centered and environmentally friendly residential environment based on interdisciplinary principles of integrating architectural, urban planning, and socio-ecological approaches.
Keywords: residential architecture; development strategies; architectural composition; urban planning; urban environment